The role of diet and physical activity in PCOS - A Quick Review - Natalia Pawelec; Weronika Mazur; Artur Hawajski; Natalia Jankowska; Adrianna Świerzyńska; Alicja Kapciak; Julia Górny; Katarzyna Naja (Quality in Sport)
Introduction: Polycystic Ovary Syndrome (PCOS) is a condition commonly found in young women. It is associated with many possible health consequences, ranging from acne, hirsutism, and obesity to fertility problems and even the development of endometrial cancer. Treatment is tailored to the individual, depending on various complications and needs. However, it is important to note that in most cases, the first recommended step is lifestyle modification. Key components of this include a healthy diet and physical activity. These recommendations are often overlooked or undervalued, with patients frequently expecting immediate pharmacological treatment and not believing in the potential effects of lifestyle changes.